PERBEDAAN JARAK TEMPAT TINGGAL DARI LOKASI INDUSTRI GENTENG TERHADAP PENURUNAN FUNGSI PARU PENDUDUK DI DESA KEDAWUNG KECAMATAN PEJAGOAN KABUPATEN KEBUMEN (Unnes Journal of Public Health, 2015)
The  process  of  tile  combustion  produced  air  pollution  in  the  form  of  dust  and  smoke  which  could  influence degradation of lung function of the people around industry. There were 143 tile industries in Kedawung Village and it located near the residences. The purpose of this study was to know the difference between distance of shelter from the location of tile industry towards degradation of lung function of people in Kedawung village Pejagoan district,  Kebumen  regency.  This  research  was  using  analytic  observational  with  cross  sectional  approach. Population in this study were the people in Kedawung village. Sample amounted to 94 persons. Data analysis was carried out by univariat and bivariat (Chi Square). The results of this study was there was a difference between  distance  of  shelter  from  location  of  tile  industry  towards  decline  in  lung  function  of  the  people  in Kedawung village Pejagoan district Kebumen regency (p=0,001). Suggestion for tile entrepreneurs is expected to make a higher chimney  and reforestation around the chimney burning, for the example planting yellow palm. For those people who expected, during the day must close the window or other ventilation, make ventilation with a filter/filter type of fiberglass with price about Rp.600.000,- per meter